Biodegradation of expanded polystyrene by mealworm larvae under different feeding strategies evaluated by metabolic profiling using GC-TOF-MS. (October 2021) - Tsochatzis, E.D.; Berggreen, I.E.; Nørgaard, J.V.; Theodoridis, G.; Dalsgaard, T.K.
Abstract: The present study investigated the biodegradation of polystyrene (PS) plastic by mealworm ( Tenebrio molitor ) on different diets followed by untargeted screening of larvae gut intestine tissue and frass (manure and feed residuals) to investigate the existence of polymer-generated organic residues. Three different diets, consisting of PS, rolled barley and water were tested. PS degradation rates ranged from 16% to 23% within 15 days, with no statistical differences in survival rates. The larvae fed with ad libitum barley:PS (20:1 w/w) and water had the highest growth rate, while higher PS consumption was observed for barley:PS of 4:1 w/w. A GC-TOF-MS analysis revealed no contaminating substances in the gut intestine tissue, nor styrene or PS oligomers, whilst several bioactive compounds and traces of alkanes, mostly with small carbon chains, were present. Metabolomics analysis on the collected frass, either on the lipophilic (CHCl3 ) or the polar fraction (MeOH–H2 O) was performed. Styrene and PS oligomers (dimers, trimers) were identified, though in a relatively low total amount, up to a total of 346.0 ng/mg 2, 4 di-tert butylphenol was identified in both frass and tissue, coming from the PS polymer (Non-intentionally added substances; NIAS). Finally, in the polar fraction of frass, bioactive molecules (fatty acids, amides) were identified, together with several hydrocarbons, mostly with longer carbon chains. The formation of these substances indicated enzymatic and biochemical activity in the larvae-gut intestine. It was shown that degrading and contaminating organic compounds occur at low levels, in both gut intestine and frass, during bio-degradation of PS. Highlights: PS consumption ranged from 16 to 23% during 15 days of feeding. Frass contained low mass fractions of plastic polymer-generated compounds. No polymer-related chemical compounds formed in insects' gut intestine tissue. GC-TOF-MS metabolic profiling performed.